Tuberculous Lymphadenitis in Manitoba: Incidence, Clinical Characteristics and Treatment - Victoria J Cook; Jure Manfreda; Earl S Hershfield (Canadian Respiratory Journal, 2004)
BACKGROUND: Tuberculous lymphadenitis (TBL) is an important form of extrapulmonary tuberculosis (TB). Recent studies have shown an increase in TBL in Canada.